The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jctb.7509
|View full text |Cite
|
Sign up to set email alerts
|

Co‐production of biobutanol and biomethane from distillers' grain waste by an integrated process

Jiang‐Bo Wang,
Hao Wang,
Jing‐Zhuo Han
et al.

Abstract: BackgroundDistillers' grain waste (DGW) is the main by‐product in the Baijiu‐making process and its management remains a great challenge for the Baijiu industry. To address this issue, an integrated biobutanol and biomethane production process was established to obtain valuable products from DGW and reduce environmental pollution.ResultsIn the integrated process, DGW was hydrolyzed and detoxified to produce biobutanol, while the distillery waste derived from solvent extraction process was used for biomethane f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…The high concentration of organics of Huangshui with some microorganisms can be used as a substrate or inoculum to treat certain types of organic wastewater for organic pollutant degradation and biofuel production. Wang et al [66] utilized the DSG containing Huangshui to co-produce biobutanol and bioCH 4 , having relatively high costs. Ling et al [11] observed that the antimicrobial activity of Huangshui could promote the oleaginous yeast to become the dominant microbes over undesirable microbes for treating mixed wastewater to produce lipids.…”
Section: Full Utilization Of Huangshui In Different Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high concentration of organics of Huangshui with some microorganisms can be used as a substrate or inoculum to treat certain types of organic wastewater for organic pollutant degradation and biofuel production. Wang et al [66] utilized the DSG containing Huangshui to co-produce biobutanol and bioCH 4 , having relatively high costs. Ling et al [11] observed that the antimicrobial activity of Huangshui could promote the oleaginous yeast to become the dominant microbes over undesirable microbes for treating mixed wastewater to produce lipids.…”
Section: Full Utilization Of Huangshui In Different Fieldsmentioning
confidence: 99%
“…Using abundant organic substances to synthesize products with high value can obtain the material virtuous cycle in the Baijiu industry [11]. Through innovating food products, optimizing fertilization structure, and paying attention to healthy foods and integrated water and fertilizer, along with eco-friendly management and reutilization strategies, the full utilization of Huangshui can be achieved, with its maximum value, ultimately impelling the sustainable developments and prosperities of the food industry and agriculture fields [10,66]. With the intensification of energy and food crises and water shortages, as well as the increasing demand for environmental protection, the full utilization of high-strength organic wastewater can alleviate the above difficulties.…”
Section: Prospectsmentioning
confidence: 99%